Android-Assisted Cardiovascular Education and Risk Screening to Improve Coronary Heart Disease Literacy in Primary Care: A One-Group Pre–Post Community Intervention in Indonesia - Sari Luthfiyah; Triwiyanto Triwiyanto; Syevana Dita Musvika; Yudha Aditya Fahriza; Alfred Rafu Neno; Rizky Dwi Sisantiara (Frontiers in Community Service and Empowerment, 2026)
Coronary heart disease (CHD) prevention in primary care is constrained by limited consultation time, uneven health literacy, and insufficient reinforcement after one-off education. This community service program evaluated a hybrid intervention combining clinician-led education, guided Android application use, and self-risk screening. The program was delivered at Candi Primary Health Center, Sidoarjo, Indonesia, on 9 June 2026 using a one-group pre-test–post-test design. Community members were recruited consecutively; paired analysis included participants who attended the intervention and completed matchable pre- and post-tests. The intervention comprised baseline assessment, structured CHD education, application demonstration, hands-on practice, and immediate post-test. Knowledge was assessed with an expert-reviewed 20-item true–false questionnaire scored from 0 to 100. Approximately 60 electronic entries were screened; after duplicate and incomplete records were removed, 13 valid paired observations remained. The mean knowledge score changed from 63.50 ± 12.05 (pre-test) to 97.00 ± 4.62 (post-test), with an absolute change of 33.50 points (95% CI: 30.09–36.91), p < 0.001, and a large effect size (Cohen’s dz = 2.54). Application access, screening completion, and assistance needs were 54 (90%), 60 (100%), and not formally assessed in the dataset, respectively. The hybrid intervention was feasible under supervised conditions and was associated with an immediate improvement in CHD literacy. However, the small uncontrolled sample, immediate outcome assessment, and absence of longitudinal usage data preclude conclusions about sustained behavior change. Integration into routine non-communicable disease education should be accompanied by cadre training, user support, and longer-term evaluation.